1996
DOI: 10.1016/0301-2115(95)02330-5
|View full text |Cite
|
Sign up to set email alerts
|

Amnioinfusion

Abstract: Abnormal amniotic fluid volume may be both the result and the cause of complications at various stages of pregnancy. This review focuses on evidence from randomised trials of the effectiveness of amnioinfusion. Attempts to prevent the development of pulmonary hypoplasia by means of transabdominal amnioinfusion to correct severe oligohydramnios in the middle trimester of pregnancy have not been evaluated by randomised trials. Long-term transcervical amnioinfusion for prelabour rupture of the membranes has shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 36 publications
0
4
0
6
Order By: Relevance
“…Amnioinfusion has also been used in women with meconium staining of the amniotic fluid. Systematic review of randomised trials has shown an overall reduction in the incidence of caesarean section, of meconium below the vocal cords and of meconium aspiration syndrome 8,9 . As thick meconium staining of the amniotic fluid is unlikely without reduction in the volume, it is not clear whether the benefits recorded in these studies are due to dilution of the meconium, or correction of oligohydramnios with elimination of fetal heart rate decelerations as discussed above.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amnioinfusion has also been used in women with meconium staining of the amniotic fluid. Systematic review of randomised trials has shown an overall reduction in the incidence of caesarean section, of meconium below the vocal cords and of meconium aspiration syndrome 8,9 . As thick meconium staining of the amniotic fluid is unlikely without reduction in the volume, it is not clear whether the benefits recorded in these studies are due to dilution of the meconium, or correction of oligohydramnios with elimination of fetal heart rate decelerations as discussed above.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid absorption of the infused fluid could account for reported cases of pulmonary oedema. We have also suggested the possibility that introduction of the uterine catheter may cause tearing of the amniotic membrane in the lower uterine segment, with the risk of escape of amniotic fluid into the circulation when the presenting part descends below the level of the breach in the amnion 9 . We suggested that these possibilities be further investigated, and that correct placement of the catheter be confirmed by aspiration of amniotic fluid prior to amnioinfusion.…”
Section: Introductionmentioning
confidence: 99%
“…La ruptura prematura de membranas ovulares (RPMO) se define como la pérdida de la continuidad de las membranas corioamnióticas antes del inicio del trabajo de parto. [1][2][3] La incidencia de RPMO pretérmino fluctúa entre 2,7 y 17% y se asocia aproximadamente a un tercio de los partos pretérmino, generando morbimortalidad fetal y morbilidad materna. [1][2][3][4] El diagnóstico de RPMO, la mayoría de las veces, se realiza por una historia clínica sugestiva y hallazgos concordantes con el examen físico al observar escurrimiento de una cantidad variable de líquido amniótico (LA) por la vagina.…”
Section: Introductionunclassified
“…[1][2][3] La incidencia de RPMO pretérmino fluctúa entre 2,7 y 17% y se asocia aproximadamente a un tercio de los partos pretérmino, generando morbimortalidad fetal y morbilidad materna. [1][2][3][4] El diagnóstico de RPMO, la mayoría de las veces, se realiza por una historia clínica sugestiva y hallazgos concordantes con el examen físico al observar escurrimiento de una cantidad variable de líquido amniótico (LA) por la vagina. 2,4 En ocasiones clínicamente no es posible hacer el diagnóstico diferencial entre las entidades que simulan la ruptura de membranas y una verdadera RPMO, lo que lleva a utilizar procedimientos complementarios, como la inyección intraamniótica de índigo carmín, cuya detección en la vagina confirma el diagnóstico.…”
Section: Introductionunclassified
See 1 more Smart Citation